Functional Changes of the Perigenual Part of the Anterior Cingulate Cortex after External Trigeminal Neurostimulation in Migraine Patients - Russo, Antonio; Tessitore, Alessandro; Esposito, Fabrizio; Di Nardo, Federica; Silvestro, Marcello; Trojsi, Francesca; De Micco, Rosa; Marcuccio, Laura; Schoenen, Jean; Tedeschi, Gioacchino (Frontiers in Neurology, 2017)
Objective: To explore the functional reorganization of the pain processing network during trigeminal heat stimulation (THS) after 60 days of external trigeminal neurostimulation (eTNS) in migraine without aura (MwoA) patients between attacks. Methods: Using whole-brain BOLD-fMRI, functional response to THS at two different intensities (41° and 51 °C) was investigated interictally in 16 adults MwoA patients before and after eTNS with the Cefaly® device. We calculated the percentage of patients having at least a 50% reduction of monthly migraine attacks and migraine days between baseline and the last month of eTNS. Secondary analyses evaluated associations between BOLD signal changes and clinical features of migraine. Results: Before eTNS treatment, there was no difference in BOLD-response between MwoA patients and HC during low-innocuous THS at 41 °C, whereas the perigenual part of the right ACC revealed a greater BOLD-response to noxious THS at 51 °C in MwoA patients when compared to HC. The same area demonstrated a significant reduced BOLD response induced by the noxious THS in MwoA patients after eTNS (p=0.008). Correlation analyses showed a significant positive correlation between ACC BOLD response to noxious THS before eTNS treatment and the decrease of ACC BOLD response to noxious THS after eTNS. Moreover, a significant negative correlation in the migraine group after eTNS treatment between ACC functional activity changes and both the perceived pain ratings during noxious THS and pre-treatment migraine attack frequency has been found. Conclusions: Our findings suggest that eTNS treatment with the Cefaly® device may induce a functional antinociceptive modulation in the ACC that may be involved in the mechanisms underlying its preventive anti-migraine efficacy.